The Selective Response Speed Test Relationship with 200m Kayak Achievement during Mental and Physical Bio Cycles - Majeed, Haider (Journal of Physical Education, 2018)
The Selective Response Speed Test Relationship with 200m Kayak Achievement during Mental and Physical Bio CyclesThe problem of the research lies in the lack of information about mental and physical cycles and their relationship with achievement. The research aimed at identifying the level of physical and mental cycles and their effect on the level of achievement and selective response speed test. the data was collected and treated using proper statistical operations to conclude that there is no relationship between selective response speed results with 200m kayak achievement. The conclusions also showed an effect of biorhythmic cycles specially the physical cycle on the level of achievement.